Pengaruh Variasi Dimensi Saluran Tuang Terhadap Fluidita, Porositas dan Kekerasan Pengecoran dengan Bahan Baku Aluminium Bekas - Sumpena (Politeknosains, 2016)
Quality casting one of which depends on the system and the sprue size, so need to analyze the effect of sprue size, till how long aluminum molten able to flowing in sand molds.With made variations diameter in gate expected to be obtained capable of a maximum flow or is able to flow most distant. This will assist in completing the castings process for cast objects with a certain length. The purpose of this study was to determine the effect of variations dimensions sprue to fluidity, porosity and hardness foundry of the raw material for aluminum scrap. Smelting process carried out in the laboratory of the foundry Department Mechanical Engineering University of Proklamasi 45 Yogyakarta. The smelting process using the crucible furnace on it be put kowi the place aluminum to be melted down. Sand mold is made of 3 pieces for each sprue 1 (d1), sprue 2 (d2), sprue 3 (d3). Patterns made with thickness 3 mm, 4 mm, 6 mm and 7 mm. The measurement results calculated averages value length fluidity for each thickness the castings. Observations the porosity was do by weighing of the castings (mass, kg) divided by the volume of the castings, so obtainable the density of the castings. Hardness testing is done with the kind of Vickers hardness test. Testing in this study using a 200 g load suppression, loading time 10 seconds, using a hardness machine types Buehler High Quality Micro Hardness Tester 0054 MM models. The testing results and observations indicate that the longest fluidity with diameter sprue 13 mm for thickness objects 3 mm and 4 mm with length is 251.7 mm and 290 mm. The fluidity longest also be obtained on castings the sprue diameter 15 mm with thick 6 mm and 7 mm is 296.86 mm and 343.33 mm. Hardness testing results show the value of the highest hardness on sprue diameter 17 mm is 107.98 VHN, while the value of the lowest hardness on sprue diameter of 15 mm is 88.3 VHN. Porosity observations showed that diameter sprue 17 mm obtained the lowest porosity level that is equal to 2.734 gr/cm3, while the level of the highest porosity is obtained on the diameter sprue13 mm castings of 2.831 gr/cm3.